Development of hydrogel-based MEMS piezoresistive sensors for detection of solution pH and glucose concentration - Thong, Trinh Quang; Guenther, Margarita; Gerlach, Gerald (Vietnam Journal of Mechanics, 2012)
Hydrogels are water-swollen polymeric materials that maintain a distinct three-dimensional structure. Manipulation of hydrogel structure has produced stimuli sensitive hydrogels, which change their swelling degree or undergo phase transition in response to minimal changes in environmental conditions. This paper presents the development of hydrogel-based sensors for measurement of solution pH and glucose concentration using commercial MEMS piezoresistive pressure transducers. pH-sensitive PVA/PAA and glucose-sensitive AAm/3-APB/BIS hydrogels are used in the experiments. Two types of sensor packaging, one is used as solution container and the other used to dip into solution have been performed. The measurements for different solutions having pH values between 1 to 11 and glucose concentrations between 2.5 mM and 15 mM have been carried out. The output characteristics of sensors have been demonstrated showing the long-term reproduction and relatively good sensitivity, namely approximately 20 mV/pH for pH sensor and 7 mV/1 mM of glucose concentration for glucose sensor.